Crotoxin-Loaded Silica Nanoparticles: A Nanovenom Approach - Florencia Silvina Conti; Exequiel Giorgi; Laura Montaldo; Juan Pablo Rodríguez; Mauricio Cesar De Marzi; Federico Gastón Baudou (Pharmaceutics)
Background: Ophidism is a globally neglected health problem. In Argentina, Crotalus durissus terrificus (C.d.t., South American rattlesnake) is one of the species of greatest medical importance since its venom contains mainly crotoxin (CTX), a potent enzyme–toxin with PLA2 activity, which is responsible for its high lethality. Objective: In this work, we aimed to generate nanovenoms (NVs), complexes formed by CTX adsorbed onto 150 nm silica nanoparticles (SiNPs), and to study their physicochemical, biological, and immunomodulatory activities for potential use as adjuvants (ADJs) in antivenom (AV) production. Methods: CTX was isolated and corroborated by SDS-PAGE. Then, CTX was adsorbed on the synthetized Stöber SiNPs’ surfaces, forming a monolayer and retaining its biological activity (as observed by the MTT cell proliferation assay using the THP-1 cell line). Results: Immunomodulatory activity revealed a high pro-inflammatory (IL-1β) response induced by SiNPs followed by NVs. In the case of the anti-inflammatory response, NVs presented significant differences for TGF-β only after cell activation with LPS. No significant differences were observed in IL-10 levels. Conclusions: Thus, these results suggest that NVs together with SiNPs could increase immunogenicity and enhance immune response, turning them into potential tools for the generation of new antivenoms.